Ontogenetic instars of the oribatid mite Eupterotegaeus nortoni sp. nov. (Acari, Oribatida, Cepheusidae) from U.S.A. - Ermilov, Sergey G. (Zootaxa, 2024)
A new species of the genus Eupterotegaeus (Oribatida, Cepheusidae) is described from the U.S.A., based on adult and juvenile instars. The revised generic diagnosis and an identification key to the known representatives of Eupterotegaeus are presented.